Implementation of WEB-based health information system at the community health center - Meiryani; Sudrajat, Jajat; Mat Daud, Zaidi; Warganegara, Dezie Leonarda (Hampstead Psychological Associates, 2020)
Hospital health management information system is an important system. This study aims to determine the application of web-based health management information systems in community health centers in Jakarta's citrus sub-district of Indonesia. This type of research is quantitative with descriptive research design. Data collection using a questionnaire. From the results of the study it was found that the implementation of a web-based health management information system at the community health center in the Jakarta citrus district of Indonesia was optimal. This can be seen from the hardware, software, procedures, brainware, database and network communication technology that is used is adequate. The number of computers is categorized as sufficient because it is already available in each service unit, the internet network has supported the implementation of a health management information system at the community health center. The software used has fulfilled the standards of minimal Windows XP software and e-Community Health Center applications. Completeness of the e-Community Health Center data is categorized as adequate. The number of operators is categorized as good because it is available in each service unit. The community health center of Kebon Jeruk District, Indonesia, has a budget for maintaining hardware, software, brainware, databases and communication technology networks that are well maintained.